Elephant numbers, group structure and movements on privately owned land adjacent to Tsavo East National Park, Kenya - McKnight, Barbara (Pachyderm, 2004)
This July 1999-Nov 2001 study, which focused on the elephants in the Rukinga Wildlife Sanctuary and Taita Ranch lying between West Tsavo and the southwest boundary of Tsavo East in the southern sector of the Tsavo ecosystem, attempted to ascertain the number of elephants, and their group sizes and structure at the population level, and to identify individuals to facilitate further research on demography and ranging behaviour at the individual level. A photographic identification file for 165 animals was compiled. The number of elephants sighted per month ranged from 65 to 292 and almost half the sightings were groups of bulls or lone bulls. Resightings were relatively low, only 37.5% of the bulls and 60.5 % of the cows were seen in the area more than once which suggests that this area is a portion of a much larger range. 14 (6 lone bulls and 2 family groups of the elephant sighted were known to have moved between the National Park and private land and to do so crossed a major highway and railway, which illustrates that the long time routes continue to be tranversed. Elephants are getting caught up in snares intended for smaller 9 animals (used for bushmeat) and may be harassed or killed due largely to conflict with herdsmen over access to water: Nine known adults had tips or sections of the trunk missing, two had deep slash wounds across the trunk, one had a snare embedded around the trunk, two had snares embedded around the leg and two died from poisoned arrow.’ This particular study augments ongoing research in the Tsavo ecosystem. (McKnight, 1995, 1996, 2000)